2022
DOI: 10.1136/bmjopen-2021-053846
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of preoperative autologous blood donation for patients with high risk of allogeneic blood transfusion in lumbar fusion surgery: a study protocol of a randomised controlled trial

Abstract: IntroductionPreoperative autologous blood donation (PABD) can be used to reduce the exposure of allogeneic blood transfusion in patients undergoing elective surgery. Better blood management to avoid anaemia and reduce allogeneic blood transfusion after spine surgery become increasingly important with development of enhanced recovery after surgery. We present here the design of a randomised controlled trial with three groups to verify the clinical effectiveness of PABD in patients at high risk of transfusion fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…3.) Our model was more accurate than the previous model 3,14,15 for preparing blood resources before elective spinal surgery, with the cost-effectiveness of the blood reserves in limited healthcare systems. 4.)…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…3.) Our model was more accurate than the previous model 3,14,15 for preparing blood resources before elective spinal surgery, with the cost-effectiveness of the blood reserves in limited healthcare systems. 4.)…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies indicated the substantial effect of intraoperative predictors. 1,3,8,9,[11][12][13][14]16 Another previous study 3 revealed the association of PRC transfusion with age, low BMI, number of fusion and fixation segments, spine deformity, and preoperative Hb level. Further, the type of lumbar spine fusion is associated with variations in intraoperative blood loss, which should be defined.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations